Primary Student Motivation and Achievement: Developing Classroom Management and Managing Positive Behaviour - García Gómez, Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2017)
Primary teachers all over the world seem to be having a difficult time when trying to motivate their students and engage them in learning. the present paper is divided into three main sections. section 1 briefly discusses the importance of creating friendly learning atmosphere and highlights some key aspects, which are conducive to increasing students’ motivation. section 2 compiles a wide range of motivational techniques that work on prevention. section 3 presents a number of activities that activate and strengthen students’ multiple intelligences. section 4 provides the reader with effective techniques to sort out problems of disruption.